A New Vision for High-Quality Preschool Curriculum - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
A high-quality preschool education can foster critical development and learning that promotes joyful, affirming, and enriching learning opportunities that prepare children for success in school and life. While preschool programs generally provide emotionally supportive environments, their curricula often fall short in advancing learning in math, early literacy, and science, and lack the necessary support for multilingual learners emerging bilingualism. Additionally, access to high-quality, effective early learning experiences may be limited and inadequate based on factors such as a childs race, location, gender, language, identified disability, and socioeconomic status. A New Vision for High-Quality Preschool Curriculum examines preschool curriculum quality for children from ages three to five, with special attention to the needs of Black and Latine children, multilingual learners, children with disabilities and children experiencing poverty in the United States. The report articulates a vision for high-quality preschool curricula for all children, grounded in an equity and justice-oriented principles from inception to implementation and evaluation.
Keywords: Education